Subcutaneous versus vaginal progesterone for vitrified–warmed blastocyst transfer in artificial cycles. Issue 2 (August 2020) - Turkgeldi, Engin; Hanege, Burcu Yilmaz; Yildiz, Sule; Keles, Ipek; Ata, Baris
Abstract: Research question: Does subcutaneous progesterone provide similar live birth or ongoing pregnancy rates as vaginal progesterone in frozen embryo transfer (FET) cycles? Design: Retrospective cohort study ( n  = 214 women), consisting of 107 women who received subcutaneous progesterone for FET in artificial cycles and 107 women receiving vaginal progesterone who were matched for age and treatment cycle rank acted as controls. All embryos were transferred in an artificial cycle with 6 mg per day oral oestradiol valerate starting on the second or third day of the menstrual cycle. Patients underwent transvaginal ultrasound on the 10th day of priming, and subcutaneous progesterone (50 mg/day) or vaginal progesterone (180 mg/day) was started if the endometrium had a trilinear pattern regardless of its thickness. Embryo transfer was carried out on the sixth day of progesterone administration. Oestradiol and progesterone were continued until a negative pregnancy test, 10 days after the transfer, or until the completion of 10th gestational week. Main outcome measures were live birth or ongoing pregnancy rates. Results: Baseline characteristics were similar between the groups. Positive pregnancy test rates (64.5% versus 58.9%; P  = 0.40; RR 1.1; 95% CI 0.89 to 1.35), live birth or ongoing pregnancy rates (39.3% versus 35.5%; P  = 0.57; RR 1.11; 95% CI 0.78 to 1.56) and miscarriage rates (29% versus 25.5%; P  = 0.68; RR 1.08; 95% CI 0.76 to 1.55) were similar in the subcutaneous progesterone and vaginal progesterone groups, respectively. Conclusions: Subcutaneous progesterone seems to be an effective alternative to vaginal progesterone in patients undergoing FET. Randomized controlled trials comparing it with different progesterone preparations, routes and protocols are needed to better define its role.